The impact of transformational leadership on the job performance of ICT employees in Palestine: The role of psychological empowerment as a mediating factor - Milhem, Marwan; Ateeq, Ali; Dawood, Saja; Alzoraik, Mohammed; Alastal, Ahmed Yahia Mustafa (International Journal of Innovative Research and Scientific Studies, 2024)
This study examined how transformational leadership affects work performance at Palestine's Ministry of Communications and Information Technology, focusing on psychological empowerment. We conducted a descriptive study on 350 full-time employees. We took a systematic sample of 183 people from this group. A systematic questionnaire collected quantitative and qualitative employee experiences. SPSS was used to analyze the data using descriptive and deductive methods. Data patterns and linkages were identified and displayed in frequency distribution tables and visual graphics. The study found that psychological empowerment mediates the relationship between transformational leadership and job performance at the Palestinian Ministry of Communications and Information Technology. Psychological empowerment greatly enhances transformational leadership's influence on workforce performance. Organizations ought to educate leaders and empower their staff to improve performance. The research found that transformational leadership combined with psychological empowerment tactics significantly improves employee engagement and performance. This study fills gaps in the literature and expands our understanding of how psychological empowerment affects work performance. The findings support the study's assumptions and emphasize the relevance of leadership strategies that empower people psychologically. This method improves job performance and suggests empowerment-focused leadership solutions for organizational leadership and policy creation to boost workplace engagement and productivity.